ANALISIS PROSES PERENCANAAN DAN EVALUASI PELAKSANAAN STANDAR PELAYANAN MINIMAL INSTALASI GAWAT DARURAT DI RSUD DR. R. SOETIJONO BLORA - Astuti, Sri Widi; Arso, Septo Pawelas; Fatmasari, Eka Yunila (Fakultas Kesehatan Masyarakat, 2017)
Hospitals that have Public Service Board status must apply Minimum Service Standards in each service, one of which is emergency service. Emergency unit plays a major role in triage, resuscitation and stabilization. In 2016, 11.36% of total visits are EU visits and in the last three years have increased. The research aim to find out how the planning process and evaluation of implementation EU MSS in RSUD dr. R. Soetijono Blora based on the Indonesia Health Ministry Regulation No. 129 of 2008 because the existing MSS documents are not yet appropriate. This research was a qualitative research with observation and descriptive analytic approach. The data were collected through in-depth interviews and field observation. To then be analyzed using P1-P2-P3 theory. The result of the research is known that in the planning process, the MSS has not been prepared well according to the standard set because of pursuing PSB requirements. The implementation process is not yet optimal so that the MSS indicator listed in the District Government Regulation No. 5 of 2010 has not all been fulfilled. The patient mortality indicator is 0.25% (standard â‰¤ 0.2%), the indicator of ability of life saving has not been measured (standard 100%), the indicator of emergency service providers who are certified valid BLS/PPGD/GELS/ALS 75% (standard 100%) and the indicator of response time in emergency medical service 2.4 minutes which is the result of observation of the researchers (standard â‰¤ 5 minutes). This is due to the many obstacles in its implementation, such as the lack of competence of human resources, lack of infrastructure and bureaucratic complexity. As for the supervision process is still not running regularly and structured. Supervisors are less coordinated, leading to misunderstandings. To overcome this, it is necessary to update the EU MSS policy and to optimize socialization, clarify the jobdesc, preparatory training reports, and active checks on the unit.